Телефорові гриби (Thelephoraceae Chevall.) Національного природного парку «Синевир» - Ачкасов, Д.; Кузнєцов, М.; Achkasov D.; Kuznetsov M. (Львівський національний університет імені Івана Франка, 2021)
Information about 8 species of fungi from the Natural Nature Park “Synevyr”, which are Thelephoraceae representatives, is given. Three Tomentella species are registered in this territory for the first time. Hydnellum peckii Banker and H. geogenium Banker are globally rare and proposed as candidates for their inclusion in the Red List of Ukraine.
Thelephoraceae representatives from the Synevyr National Nature Park.
Keywords: fungi; biodiversity; Thelephoraceae; Synevyr; National Nature Park; Basidiomycota